Collaborative Improvement of Structure Shape and Surface Integrity in Titanium Alloy Hole Burnishing - Jiahui Liu; Pingfa Feng; Zibiao Wang; Jianfu Zhang; Feng Feng; Xiangyu Zhang (Chinese Journal of Mechanical Engineering)
Abstract In the aerospace field, hole burnishing enhancement plays an essential role in improving the service performance of load-bearing holes. To satisfy the assembly accuracy and strength requirements, the structure shape and surface integrity must be considered simultaneously during the enhancement process. The current manufacturing process of hole burnishing has a relatively weak balance between the structure shape and surface integrity; therefore, it is necessary to analyze the mechanism and optimize the parameters to improve the strengthening effect of the holes. In this study, a two-dimensional longitudinal simplified model for the hole burnishing process was established, and the reasons for the surface roughness improvement of the hole wall and material accumulation on the upper surface were analyzed. Experiments were conducted to determine the influence of the burnishing parameters on the structure shape (material accumulation, shape contour, and roundness) and surface integrity (surface roughness, residual stress, and surface hardness), based on the opposite requirements of improving the structure shape and surface integrity for the burnishing depth (BD). The results showed that with an increase in the BD, the structure shape deteriorated, whereas the surface integrity improved. Fatigue behavior verification experiments were conducted, and parameter selection schemes for the collaborative improvement of the structure shape and surface integrity were discussed. For the holes of titanium alloy TB6 (Ti-10V-2Fe-3Al), the fatigue life can be increased by 162% when the BD, spindle speed, and feed rate were 0.20 mm, 200 r/min, and 0.2 mm/r, respectively.